(untitled) (The Review of Diabetic Studies, 2025)
Objective. To synthesize the evidence (last 5 years) on how perioperative analgesia and nutritional optimization modulate the metabolic response to surgical stress and cardiovascular outcomes, integrating cardiology and anesthesiology recommendations. Methods. Narrative review of recent guidelines and meta-analyses (2021–2025) in official databases and portals. Results. ERAS protocols with multimodal analgesia/opioid sparing reduce opioid consumption, accelerate extubation, and shorten length of stay without worsening pain control; in addition, they are associated with fewer complications, with potential indirect hemodynamic benefit (e.g., reduced delirium, nausea, hypoventilation) (Othenin-Girard et al., 2025; Loria et al., 2022). Perioperative immunonutrition decreases infectious complications ( 30% relative reduction) in upper gastrointestinal surgery (Matsui et al., 2024) and the ESPEN 2025 guidelines reinforce systematic nutritional assessment and support (Weimann et al., 2025). Risk stratification and perioperative cardiovascular management follow the 2022 ESC guidelines, which recommend stepwise assessment, antiplatelet management/anticoagulation, and risk-based MINS/troponin surveillance (Halvorsen et al., 2022). Careful glycemic control (target ≤180 mg/dL in early cardiac surgery) is standard for reducing complications (AHRQ, n.d.) and 2023 reviews update algorithms for perioperative dysglycemia (Sreedharan et al., 2023). Conclusion. Integrating opioid-sparing multimodal analgesia, risk-based nutritional support, and current cardiovascular guidelines improves metabolic markers and could mitigate perioperative cardiovascular events by modulating surgical stress and myocardial demand.